2013
DOI: 10.1097/pgp.0b013e3182590ae8
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Brenner Tumor

Abstract: Extraovarian Brenner tumors are extremely rare. We report a case of vaginal Brenner tumor occurring in an 84-year-old woman. The tumor presented with vulvar irritation and soreness and consisted of a 1.8-cm polypoid mass arising from the lower third of the vagina. Microscopically, it had all the 3 components--urothelial islands, glands, and fibrous stroma--characteristic of a Brenner tumor. We suggest that vaginal Brenner tumors arise from a metaplastic process within the mullerian epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Sixteen cases of extraovarian Brenner tumors have been reported to date. They have been described in the lower abdomen or pelvic cavity such as the broad ligament and vagina, and in the testicular and paratesticular area [2, 3]. Here, we report a peculiar case of extraovarian Brenner tumor arising in the omentum that has not so far been reported in the English literature.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Sixteen cases of extraovarian Brenner tumors have been reported to date. They have been described in the lower abdomen or pelvic cavity such as the broad ligament and vagina, and in the testicular and paratesticular area [2, 3]. Here, we report a peculiar case of extraovarian Brenner tumor arising in the omentum that has not so far been reported in the English literature.…”
Section: Introductionmentioning
confidence: 80%
“…Ruthy Shco-Levy et al reported an extraovarian Brenner tumor that developed in the right distal vaginal wall and investigated the prior reported cases of extraovarian Brenner tumor in the English literature [2]. They found that 14 cases of extraovarian Brenner tumor have been reported with 5 in the vagina, 4 in the broad ligament, 3 in the testis, 1 in the uterus, and 1 in the paratesticular area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the ovary, it has been reported that BTs may also involve extraovarian tissues. Extraovarian BTs (EOBTs) are extremely rare and mainly occur around the female reproductive system such as the uterus [2,3], vagina [4][5][6][7][8], broad ligament [9][10][11][12], and omentum [13]. Another intriguing clinical observation is that EOBTs were observed occasionally in the testis [14][15][16][17] or epididymis [18], further evoking concerns regarding their origins and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Brenner tumors are classified into three categories according to the World Health Organization, namely benign, borderline and malignant (3). Extraovarian Brenner tumors are extremely rare, and are mainly found in the broad ligament, uterus, vagina, testis and epididymis (4)(5)(6)(7). In the present study, we report a case of Brenner tumor of the right testis and discuss the clinical and pathological characteristics of this disease.…”
Section: Introductionmentioning
confidence: 99%